2017
DOI: 10.1007/s12032-017-1018-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and identification of risk factors for trastuzumab-induced cardiotoxicity in breast cancer patients: an audit of a single “real-world” setting

Abstract: Management of human epidermal growth factor receptor-2-positive (HER2+) breast cancer patients includes the combination of adjuvant chemotherapy and trastuzumab. A meta-analysis reported that <5% of HER2+ breast cancer patients will develop trastuzumab-induced cardiotoxicity (TIC). Observational data suggest that incidence is much higher. We aimed to determine the incidence, time to development, and risk factors associated with TIC among less selected patients. A retrospective cohort study was carried out in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…This study has recognized a number of factors associated with significant increases in TIC, including tumor site (unilateral vs. bilateral), breast surgery, and concomitant taxane chemotherapy. Other studies have reported a diverse number of risk factors that include elderly age,[21] African ethnicity,[22] overweight,[23] mastectomy surgery,[24] concurrent anthracyclines,[25] baseline LVEF value,[26] underlying cardiac conditions,[27] and diabetes. [28]…”
Section: Discussionmentioning
confidence: 99%
“…This study has recognized a number of factors associated with significant increases in TIC, including tumor site (unilateral vs. bilateral), breast surgery, and concomitant taxane chemotherapy. Other studies have reported a diverse number of risk factors that include elderly age,[21] African ethnicity,[22] overweight,[23] mastectomy surgery,[24] concurrent anthracyclines,[25] baseline LVEF value,[26] underlying cardiac conditions,[27] and diabetes. [28]…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of immune-mediated myocarditis is possibly underreported in clinical trials given cardiac assessments were not routinely performed and trial patients may have less comorbidities. Emerging evidence suggests that the real-world rates of cardiotoxicity is higher than previously reported [12,22].…”
Section: Discussionmentioning
confidence: 80%
“…In the clinical setting trastuzumab-induced myocardial dysfunction is potentiated by prior treatment with anthracyclines, which is also supported by preclinical studies [34][35][36][37]. Other risk factors include age > 65 years, high body mass index > 30 kg/m 2 , hypertension, and lower LVEF at baseline, while there are still conflicting data on other cardiovascular risk factors as diabetes, coronary artery disease, valvular dysfunction, and left ventricular hypertrophy [34,38]. Trastuzumab-induced left ventricular dysfunction is to some extent reversible when paused or discontinued [10,[39][40][41].…”
Section: Her2 Targeted Drugsmentioning
confidence: 89%